Association between popliteal artery wall thickness and structural progression in patients with symptomatic knee osteoarthritis. (16th August 2022) - Wang, Yuanyuan; Pontoh, Ega Wirayoda; Hussain, Sultana Monira; Lim, Yuan Z; Jones, Graeme; Hill, Catherine L; Wluka, Anita E; Tonkin, Andrew; Ding, Changhai; Cicuttini, Flavia M
Abstract: Objective: There is increasing evidence for the involvement of vascular disease in the pathogenesis of knee OA. Popliteal artery wall thickness can be used as a surrogate marker of atherosclerosis. We examined the association between popliteal artery wall thickness and knee cartilage volume in individuals with symptomatic knee OA. Methods: This prospective cohort study analysed 176 participants from a randomized placebo-controlled trial examining the effect of atorvastatin on structural progression in knee OA. The participants underwent MRI of the study knee at baseline and 2-year follow-up. Popliteal artery wall thickness and tibial cartilage volume were measured from MRI using validated methods. The top quartile of the rate of tibial cartilage volume loss was defined as rapid progression. Results: At baseline, every 10% increase in popliteal artery wall thickness was associated with 120.8 mm 3 (95% CI 5.4, 236.2, P  = 0.04) lower of medial tibial cartilage volume and 151.9 mm 3 (95% CI 12.1, 291.7, P  = 0.03) lower of lateral tibial cartilage volume. Longitudinally, for every 10% increase in popliteal artery wall thickness, the annual rate of medial tibial cartilage volume loss was increased by 1.14% (95% CI 0.09%, 2.20%, P  = 0.03), and there was a 2.28-fold (95% CI 1.07, 4.83, P  = 0.03) risk of rapid progression of medial tibial cartilage loss, adjusted for age, sex, BMI, tibial bone area, smoking, vigorous physical activity, and intervention group allocation. Conclusion: The findings support a role for vascular pathology in the progression of knee OA. Targeting atherosclerosis has the potential to improve outcomes in knee OA.